Nanocatalysis for Chemical Synthesis - Purohit, Gunjan; Rawat, Manish; Rawat, Diwan S. (Synlett, 2025)
The development of heterogeneous catalytic systems for organic conversions was one of the best discoveries as it revolutionized the industrial processes. Nanocatalysts were proposed as the best alternative to make these industrial processes clean, green, and sustainable as they possess the characteristics of both homogeneous and heterogeneous catalysis, and at the same time reduce the drawbacks associated with them. For these reasons, nanocatalysis has gained much attention over the past few decades because they play a vital role in consumer markets, but also importantly business to business markets (B2B). In this context, nanocatalysts involving cheap metals, like copper, zinc, etc., have gained popularity they make these processes economically viable. Although, in industrial processes noble metal based nanomaterials, such as Pd, Pt, and Au, are regarded as among the most active catalysts, the latest advancements have shown significant opportunities and prospects for developing various nanocatalysts using elements that are abundant in nature and follow the principles of green chemistry. Various copper- and zinc-based nanocatalytic system have been synthesized using renewable precursors, like malachite, and their catalytic potential was explored for the preparation of various biological active molecules, such as spiropyrrolines, aminoindolozines, pyrrolo[1,2-a]quinolones, isoquinolones, etc., under green reaction condition. This account summarizes our contributions in the design and development of diverse nanocomposites utilizing nature abundant metals and their catalytic potential for diverse organic conversions following the green chemistry principles thus making the processes more sustainable.1 Introduction2 Magnetically Recoverable Nanocomposites3 Alumina/Silica-Based Nanocomposites4 Metal Oxide and Metal Oxide Supported Nanocomposites5 Graphene Oxide Based Nanocomposites6 Miscellaneous7 Overview8 Conclusion
Keywords: nanocatalysis; green chemistry; heterocycles; heterogeneous catalysis; medicinal chemistry; multicomponent reaction; nanostructures